Formation of Atomically Thin Co Layer on Ru Nanoparticles through Surface Limited Redox Replacement of Underpotentially Deposited Zn - Suyama, Kyota; Muramatsu, Keisuke; Sugimoto, Wataru (Meeting abstracts (Electrochemical Society), 2024)
In order to promote the widespread commercialization of polymer electrolyte fuel cells, highly active electrocatalysts are necessary to reduce the usage of scarce and expensive Pt electrocatalysts. Among various approaches, alloying with non-Pt metals and/or fabricating core-shell structures have been recognized as effective methods to optimize the electronic state of Pt and enhance catalytic activity while reducing Pt loading. 1 One ideal catalyst design to maximize Pt utilization involves depositing atomic layers of Pt onto heterogeneous metal surfaces. We have prepared Ru-core@Pt-shell nanostructures by using underpotentially deposited (UPD) Cu on Ru nanostructures and subsequent replacement with Pt atomic layers (Surface Limited Redox Replacement; SLRR). 2 In this study, we aimed to control the electronic state of Pt atomic layer on Ru by using a Co-interlayer; i.e. Ru-core@Co-interlayer@Pt-shell nanoparticles. Since Co cannot be replaced with UPD-Cu, we investigated a synthetic route involving UPD of Zn followed by Co replacement through SLRR. Ru nanoparticles supported on carbon (Ru(np)/C) with particle sizes of approximately 1–3 nm was synthesized according to a previous literature. 3 Cyclic voltammetry of Ru(np)/C in an electrolyte solution containing Zn ions was conducted to examine the UPD potential (–0.10 to 0.85 V vs. RHE, 20 mV s –1 , pH 11.2). Reduction current was observed near 0 V vs. RHE in the cathodic scan. The deposition potential of Zn in a solution with pH 11.2 was –0.44 V vs. RHE, while the hydrogen evolution potential was 0 V vs. RHE. Therefore, the reduction current most likely originates from UPD of Zn and hydrogen evolution. In the anodic scan, a peak attributed to oxidation of underpotentially deposited Zn was observed near 0.25 V vs. RHE. Subsequently, the Zn deposition amount was calculated by stripping of Zn after maintaining the potential at –0.04 V. The amount corresponds to approximately 40–50% of the ECSA of Ru(np). This result supports the deposition of Zn as atomic layers via UPD. After Zn deposition, Co was deposited through SLRR by immersing the electrode in an aqueous solution containing Co ions. EDS analysis showed a presence of Co and decrease in relative Zn content to Ru compared to Ru(np)/C sample after Zn UPD. Thus, it is suggested that Ru-core@Co-shell nanoparticles were synthesized via Zn UPD. References V. Stamenkovic, B. S. Mun, K. J. J. Mayrhofer, P. N. Ross, N. M. Markovic, J. Rossmeisl, J. Greeley and J. K. Nørskov, Angew. Chem. Int. Ed. , 45 , 2897 (2006). D. Takimoto, T. Ohnishi, J. Nutariya, Z. Shen, Y. Ayato, D. Mochizuki, A. Demortière, A. Boulineau and W. Sugimoto, J. Catal. , 345 , 207 (2017). Y. Takasu, T. Fujiwara, Y. Murakami, K. Sasaki, M. Oguri, T. Asaki and W. Sugimoto, J. Electrochem. Soc. , 147 , 4421 (2000). Figure 1